Mixed Matrix Membranes with Excellent CO2 Capture Induced by Nano‐Carbon Hybrids. Issue 8 (27th June 2017) - Pan, Xinglong; Zhang, Jianqiang; Xue, Qingzhong; Li, Xiaofang; Ding, Degong; Zhu, Lei; Guo, Tianchao
Abstract: 1 D multi‐walled carbon nanotube/graphene oxide nanoribbon (MWCNT@GONRs) hybrids were prepared using a chemical method as fillers for Pebax‐based mixed matrix membranes (MMMs) with excellent CO2 separation performance. Herein, the GONRs shell provided a selective barrier and large gas adsorption area, which contributed to enhancement of gas selectivity, while MWCNTs core with smooth internal surface acted as a rapid transport channel, which improved the gas permeability. It is found that MMMs with 1 wt % loading showed the highest separation factor (80 for CO2 /N2 and 23 for CO2 /CH4 ) and high CO2 permeability, far surpassing the upper bound line. Therefore, the synergistic effect of the MWCNTs core and GONRs shell in MWCNT@GONRs nanohybrids can effectively enhance the gas‐separation performance of MMMs at low loading. The unique microstructures, ease of synthesis and low filled loading make MWCNT@GONRs promising candidates in post‐combustion and sustainable chemistry. Abstract : As a novel filler, 1 D multi‐walled carbon nanotube/graphene oxide nanoribbons (MWCNT@GONRs) with low oxidation degree can enhance the gas‐separation performance of mixed matrix membranes (MMMs) due to the synergistic effect of the MWCNTs core and GONRs shell.